2013
DOI: 10.1155/2013/474028
|View full text |Cite
|
Sign up to set email alerts
|

Higher Levels of Autoantibodies Targeting Mutated Citrullinated Vimentin in Patients with Psoriatic Arthritis Than in Patients with Psoriasis Vulgaris

Abstract: Antibodies against citrullinated proteins/peptides (ACPAs), and especially antibodies targeting mutated citrullinated vimentin (anti-MCVs), are novel biomarkers of rheumatoid arthritis (RA). Whereas ACPAs are specific and sensitive markers for RA, there have hardly been any reports relating to ACPAs in psoriatic arthritis (PsA) or in psoriasis without joint symptoms (PsO). The aim of the present study was to investigate the prevalence of anti-MCVs in PsA and PsO. Serum anti-MCV titers were measured in 46 PsA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 47 publications
3
17
0
1
Order By: Relevance
“…This observation is well in line with the study of Dalm ady et al where similar inverse correlation between the level of anti-mutated citrullinated vimentin and the age of Ps onset was detected, while this correlation was not seen in the PsA group. 24 Our study provides evidence for the presence of anti-a6integrin antibodies in psoriasis. Whether the observed autoantibody production is exclusively a result of the pathomechanism or it excites the development of the disease still remains unclear, and requires further elucidation.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…This observation is well in line with the study of Dalm ady et al where similar inverse correlation between the level of anti-mutated citrullinated vimentin and the age of Ps onset was detected, while this correlation was not seen in the PsA group. 24 Our study provides evidence for the presence of anti-a6integrin antibodies in psoriasis. Whether the observed autoantibody production is exclusively a result of the pathomechanism or it excites the development of the disease still remains unclear, and requires further elucidation.…”
Section: Discussionsupporting
confidence: 52%
“…This observation is well in line with the study of Dalmády et al . where similar inverse correlation between the level of anti‐mutated citrullinated vimentin and the age of Ps onset was detected, while this correlation was not seen in the PsA group …”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Carbamylation may thus be relevant in inducing autoimmunity in PsA, and given its systemic effects, it may represent a trigger for metabolic pathways such as anaerobic cysteine metabolism and oxidative stress in PsA [183]. Authors investigated the prevalence of anti-MCV in PsA patients and reported that anti-MCV levels were significantly higher in PsA patients than those in patients with psoriasis [184]. Moreover, the presence of tender knee joints and nail psoriasis resulted significantly associated with anti-MCV positivity in the PsA group [184].…”
Section: Authorsmentioning
confidence: 99%